2004
DOI: 10.2174/1566523043346372
|View full text |Cite
|
Sign up to set email alerts
|

Transductional Targeting of Adenoviral Cancer Gene Therapy

Abstract: Adenoviral gene therapy has shown promise in both preclinical and clinical settings, but several hurdles need to be overcome before it can reach its full therapeutic potential. One such hurdle is the need for targeting the right cell type, while avoiding liver uptake and hence side effects. This review will focus on transductional targeting strategies, in which the adenoviral particle is physically targeted to specific surface receptors expressed on the target cell. This can be achieved by using either bifunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…Changes in the expression of PM proteins can also be detected with transductionally targeted recombinant viruses, which are able to enter only those cells with the appropriate ligand exposed on the PM. This has been accomplished in cancer cells already and readers are referred to an excellent review by Everts and Curiel for more information (Everts and Curiel, 2004). A similar strategy could be used to target senescent cells.…”
Section: Plasma Membrane-associated Proteinsmentioning
confidence: 99%
“…Changes in the expression of PM proteins can also be detected with transductionally targeted recombinant viruses, which are able to enter only those cells with the appropriate ligand exposed on the PM. This has been accomplished in cancer cells already and readers are referred to an excellent review by Everts and Curiel for more information (Everts and Curiel, 2004). A similar strategy could be used to target senescent cells.…”
Section: Plasma Membrane-associated Proteinsmentioning
confidence: 99%
“…205 Although the complexities of HSV-1 entry are not fully unraveled, several studies have demonstrated the feasibility of restricting HSV-1 infection to predefined subpopulations of cells (reviewed in Burton et al 13 ). For example, an HSV-1 mutant was engineered in which the heparan sulfate binding domain of gB was abrogated, and N-terminal truncated gC was fused to full-length erythropoietin (EPO).…”
mentioning
confidence: 99%
“…This can be achieved by redirecting binding of the vector to molecules highly expressed on tumor cell surfaces. This approach has been most widely applied in the context of Ad, as reviewed by Everts et al (31). The adenovirus capsid is comprised of three major protein components-the hexon, penton base and fiber/knob.…”
Section: Immunopotentiation Gene Therapymentioning
confidence: 99%